The supernatural in Tudor and Stuart England - Oldridge, Darren 1966- (Routledge, 2016)
"The Supernatural in Tudor and Stuart England reflects upon the boundaries between the natural and the otherworldly in early modern England as they were understood by the people of the time. The book places supernatural beliefs and events in the context of the English Reformation to show how early modern people reacted to the world of unseen spirits and magical influences. It sets out the conceptual foundations of early modern encounters with the supernatural, and their attempts to establish natural explanations for supernatural events"...